The Effectiveness of Phonics Method in Improving English Pronunciation to 5th Grade Students at SD GMIM IV Tomohon: Efektivitas Metode Fonik dalam Meningkatkan Pengucapan Bahasa Inggris pada Siswa Kelas 5 di SD GMIM IV Tomohon - Elsinta Cristiani Lumi; Ceisy N. Wuntu; Olga Rorintulus (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study investigates the effectiveness of the Phonics Method in improving English pronunciation among 5th-grade students at SD GMIM IV Tomohon. With increasing emphasis on oral communication in Indonesia’s elementary English curriculum, mastering pronunciation at an early stage becomes crucial. However, students often struggle with phonological differences between Indonesian and English, such as vowel sounds, consonant clusters, and word stress. The Phonics Method, which systematically teaches the relationship between graphemes and phonemes, is proposed as an alternative to traditional pronunciation instruction methods. Using a mixed-method design, this study involved two groups: an experimental group taught with Phonics Method and a control group receiving conventional instruction. Quantitative data were collected through pre-tests and post-tests, while qualitative insights were gathered via classroom observation, student questionnaires, and teacher interviews. The findings revealed significant improvement in the pronunciation skills of students taught using the Phonics Method, especially in vowel and consonant articulation, syllable awareness, and word stress. Students also demonstrated higher engagement and confidence. The results suggest that phonics-based instruction enhances not only segmental features of pronunciation but also supports better learning motivation and participation. This study concludes that integrating the Phonics Method in elementary English instruction can effectively address early pronunciation difficulties and foster sustainable language acquisition